2019
DOI: 10.1037/law0000209
|View full text |Cite
|
Sign up to set email alerts
|

Rapport building in suspect interviewing: A comparison of relationship- and procedure-based approaches in a laboratory setting.

Abstract: Both researchers and practitioners have stressed the importance of developing rapport in the investigative interviewing of criminal suspects. There is, however, no clear definition of what constitutes rapport and ways of achieving and maintaining rapport. Most research on rapport building with suspects have focused on a positive personal bond between the investigator and suspect (i.e., relationship-based approach), while more recent research suggests the merits of a neutral type of rapport building that focuse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Moreover, our exploratory analysis showed that participants who perceived higher rapport with the investigator in terms of cultural similarity also provided more central and correct details, suggesting a benefit of cultural affiliation. There is emerging evidence demonstrating that cultural background plays a key role in how interviewees communicate and build relationships with interviewers (Beune et al., 2010; Huang & Teoh, 2019; Wachi et al., 2014). In cross‐cultural interviews (where interviewees and investigators are from different backgrounds), building rapport can be challenging due to varying cultural norms related to verbal and non‐verbal communication (Abbe & Brandon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our exploratory analysis showed that participants who perceived higher rapport with the investigator in terms of cultural similarity also provided more central and correct details, suggesting a benefit of cultural affiliation. There is emerging evidence demonstrating that cultural background plays a key role in how interviewees communicate and build relationships with interviewers (Beune et al., 2010; Huang & Teoh, 2019; Wachi et al., 2014). In cross‐cultural interviews (where interviewees and investigators are from different backgrounds), building rapport can be challenging due to varying cultural norms related to verbal and non‐verbal communication (Abbe & Brandon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rapport can be promoted by both nonverbal ( Collins et al, 2002 ) and verbal approaches ( Krix and Sauerland, 2013 ; Vallano and Schreiber Compo, 2011 ). Moreover, relationship-based or procedurally-based rapport can be established ( Huang and Teoh, 2019 ). In particular, beneficial techniques are direct reactions to the other person, active listening, mirroring, self-revelation, showing similarities, continuous and repeated contact, and contrasting ( Kelly et al, 2013 ; cf.…”
Section: Communicationmentioning
confidence: 99%
“…However, the use of rapport-based interviewing tactics during interviews appears to be effective in reducing such strategies (Alison et al, 2014a). In experimental studies, building rapport has also been shown to increase cooperation and admissions from individuals in both Western (Brimbal et al, 2019; Evans et al, 2014) and non-Western populations (Huang & Teoh, 2019; Wachi et al, 2018). Field and observational data suggest that rapport-based tactics facilitate information obtained from real-world suspects (Alison et al, 2013; K. Collins & Carthy, 2019; C. E. Kelly et al, 2016; Walsh & Bull, 2012); human intelligence sources (Nunan et al, 2020); and victims of crime (Kim et al, 2020).…”
Section: Self-disclosurementioning
confidence: 99%